The Role of Brand Trust in Mediating the Influence of Product Quality on Repurchase Intention at Imadji coffee in Denpasar City - I Putu Kalvin Lingga Pratama; I Gde Ketut Warmika (LPPM STIE Kasih Bangsa, 2025)
The promising growth of the coffee industry presents new challenges in retaining consumers in the long term amid an increasingly crowded and dynamic market. This situation is also experienced by one of the coffee shops in Bali, particularly in Denpasar City, namely Imadji coffee. This study aims to explain the role of brand trust in mediating the influence of product quality on repurchase intention at Imadji coffee. The research was conducted in Denpasar City by distributing online questionnaires to 120 respondents. The sampling technique used was non-probability sampling with a purposive sampling method. The results of the study show that all hypotheses are accepted. Product quality has a positive and significant effect on repurchase intention. Product quality has a positive and significant effect on brand trust. Brand trust has a positive and significant effect on repurchase intention. Brand trust is able to partially mediate the effect of product quality on repurchase intention. The implications of this study support consumer behavior theory and the S-O-R model, while emphasizing the importance of maintaining product quality to build brand trust, thereby increasing repurchase intention at Imadji coffee in Denpasar City.